PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA DASAR BERBASIS LITERASI SAINS DENGAN MENGGUNAKAN GOOGLE SITES - Reza Ruhbani Amarulloh (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2022)
The purpose of this study is to develop a learning media for fundamentals physics course based on scientific literacy using the Google Sites platform. This study was carried out using the Research and Development method with Borg and Gall's (1989) development design. The developed media was validated by nine science learning media experts and tested on 31 students of fundamentals physics course on temperature and heat topic to determine the user's response. The results shows that the developed media is valid and suitable for use with very good classification, which includes: content quality, learning objectives suitability, feedback and adaptation, motivation, presentation design, interaction usefulness, and accessibility. User response to the developed media is positive in aspects which include; Attractiveness, clarity, efficiency, reliability, stimulation and novelty. It can be concluded that the developed learning media is feasible to use in fundamentals physics course